2007
DOI: 10.1007/s10565-007-9046-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of comet assay in measuring DNA damage and repair efficiency in child, adult, and old age populations

Abstract: In the present study, we used the Comet assay to estimate basal DNA damage in three distinct populations aged 5-10, 40-50, and 60-70 years old. The DNA damage induced by hydrogen peroxide and gamma-irradiation in the lymphocytes of these populations, as well as their repair activity, was also studied. Finally, we measured apoptosis and necrosis after the effect of these agents. Our results indicate that the older population (60-70 years old) showed higher basal levels of DNA damage and was more sensitive to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 44 publications
3
23
1
Order By: Relevance
“…2). Our observations conformed to the data reviewed by Møller et al [38,39], but conflicting findings have shown an age-dependent sensitivity of populations to chromosomal breakage [40] and DNA damage [41]. Nevertheless, a three-to eightfold increase in the percentage of sensitive individuals, associated with accumulation of unrepaired H 2 O 2 -induced lesions, was observed in the subgroup of elderly workers ( Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…2). Our observations conformed to the data reviewed by Møller et al [38,39], but conflicting findings have shown an age-dependent sensitivity of populations to chromosomal breakage [40] and DNA damage [41]. Nevertheless, a three-to eightfold increase in the percentage of sensitive individuals, associated with accumulation of unrepaired H 2 O 2 -induced lesions, was observed in the subgroup of elderly workers ( Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…Hazane et al [43] and Sauvaigo et al [44], using also the comet assay, found that aging was associated with decreased DNA-repair capacity. Piperakis et al [45] demonstrated that older persons have increased levels of DNA damage and a less efficient DNA-repair system in comparison with young persons. Increased DNA damage by older age as detected by the comet assay was also reported in other studies [46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ), one of the main ROS, is known to cause DNA damage in various cell types (7). Also, Caspase-3, a cysteine protease that is one of the effectors of apoptosis and necrosis, is activated by H 2 O 2 (8). …”
mentioning
confidence: 99%